Creating Clinical Reasoning Assessment Tools in Different Languages: Adaptation of the Pediatric Emergency Medicine Script Concordance Test to Japanese - Nomura, Osamu; Itoh, Taichi; Mori, Takaaki; Ihara, Takateru; Tsuji, Satoshi; Inoue, Nobuaki; Carrière, Benoit (Frontiers in Medicine, 2021)
Introduction: Clinical reasoning is a crucial skill in the practice of pediatric emergency medicine and a vital element of the various competencies achieved during the residency training. Pediatric emergency physicians are often required to stabilize patients and make correct diagnoses with limited clinical information, time and resources. The Pediatric Emergency Medicine Script Concordance Test (PEM-SCT) has been developed specifically for assessing physicians’ reasoning skills in the context of the uncertainties in pediatric emergency practice. In this study, we developed the Japanese version of the PEM-SCT (Jpem-SCT) and argued the validation by collecting relevant evidence. Methods: The Jpem-SCT was developed by translating the PEM-SCT into Japanese using the Translation, Review, Adjudication, Pretest, Documentation team translation model for proper translation and cross-cultural and linguistic equivalences between the English and Japanese version of the survey. First, fifteen experienced pediatricians participated in the pre-test session, serving as a reference panel for modifying the test descriptions, incorporating Japanese context and establishing the basis for the scoring process. Then, a 1-hour test containing 60 questions was administered to 75 trainees from three academic institutions. Following data collection, we calculated the item-total correlations of the scores to optimize selection of the best items in the final version of the Jpem-SCT. The reliability of the finalized Jpem-SCT was calculated using Cronbach’s alpha coefficient for ensuring generalization of the evidence. We also conducted multiple regression analysis of the test score to collect evidence on validity of the extrapolation. Results: The final version of the test, based on item-total correlation data analysis, contained 45 questions. The participants’ specialties were as follows: Physician interns 12.0%, pediatric residents 56.0%, emergency medicine residents 25.3%, and PEM fellows 6.7%. The mean score of the final version of the Jpem-SCT was 68.6 (SD 9.8). The reliability of the optimized test (Cronbach’s alpha) was 0.70. Multiple regression analysis showed that being a physician intern was a negative predictor of test scores, indicating that clinical experience relates to performance on the Jpem-SCT. Conclusion: This pediatric emergency medicine Script Concordance Test was reliable and valid for assessing the development of clinical reasoning by trainee doctors during residency training.